The Changing Modes of Administrative Reform in South Korea - Chonghee HAN; Sunhyuk KIM (Transylvanian Review of Administrative Sciences, 2017)
In this paper, we review the past two decades of administrative reform in South Korea and argue that the dominant models and theories in the fi eld, i.e., New Public Management (NPM), post-NPM, and traditional public administration have been in a state of fusion in implementing measures without a coherent reform model. We observe that the reform movements can neither challenge nor undermine the traditional bureaucracy and maintain that they are the result of a complex mix of both environmental events and contextual factors. We specifi cally examine the co ncrete change and development of administrative reform during the Kim Dae Jung (1998- 2003), Roh Moo Hyun (2003-2008), and Lee Myung Bak (2008-2013) administrations in South Korea. Among the cases being considered are the restructuring of government ministries, the executive agency system, and rationalization of public enterprises, as well as such performance management schemes as the evaluation system for government departments and the Open Position System. We conclude that the developmental state and the hierarchical bureaucracy are still salient in South Korea’s inconsistent administrative reform since the 1990s and that it is crucial to design a prudent reform strategy to achieve a more effective public sector.